Contract Cheating in Higher Education Global Perspectives on Theory, Practice, and Policy - Eaton, Sarah Elaine; Curtis, Guy J.; Stoesz, Brenda M.; Clare, Joseph; Rundle, Kiata; Seeland, Josh. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This edited volume-the first book devoted to the topic of contract cheating-brings together the perspectives of leading scholars presenting novel research. Contract cheating describes the outsourcing of students' assessments to third parties such that the assignments or exams students submit are not their own work. While research in this area has grown over the past five years, the phenomenon has been exacerbated by the COVID-19 pandemic. Themes addressed in this book include the definition of contract cheating, its prevalence in higher education, and what motivates students to engage in it. Chapter authors also consider various interventions that can be used to address contract cheating's threat to academic integrity in higher education including: assessment practice, education, detection strategies, policy design, and legal interventions.
Chapter 1: Introduction: Contract cheating and introduction to the problem -- Chapter 2: What can we learn from measuring crime when looking to quantify the prevalence and incidence of contract cheating?- Chapter 3: Limitations of contract cheating research -- Chapter 4: Essay mills and contract cheating from a legal point of view -- Chapter 5: Leveraging college copyright ownership against file-sharing and contract cheating websites -- Chapter 6: The encouragement of file sharing behaviours through technology and social media: Impacts on student cheating behaviours and academic piracy -- Chapter 7: Higher education assessment design -- Chapter 8: Critical thinking as an antidote to contract cheating -- Chapter 9: Contract cheating and the Dark Triad traits -- Chapter 10: Contract cheating: The influence of attitudes and emotions -- Chapter 11: Applying situational crime prevention techniques to contract cheating -- Chapter 12: Presentation, Properties and Provenance: the three Ps of identifying evidence of contract-cheating in student assignments -- Chapter 13: "(Im)possible to prove": Formalising academic judgement evidence in contract cheating cases using bibliographic forensics -- Chapter 14: Aligning academic quality and standards with academic integrity -- Chapter 15: Addressing contract cheating through staff-student partnerships -- Chapter 16: The extortionate cost of contract cheating -- Chapter 17: The rise of contract cheating in graduate education -- Chapter 18: Listening to ghosts: A qualitative study of narratives from contract cheating writers from the 1930s onwards -- Chapter 19: Assessment brokering and collaboration: Ghostwriter and student academic literacies -- Chapter 20: Conclusion. .
Keywords: Education, Higher; Educational tests and measurements; Educational psychology; Schools; Education and state; Education-Research.; Higher Education; Assessment and Testing; Educational Psychology; School and Schooling; Educational Policy and Politics; Educational Research